2019
DOI: 10.1371/journal.pone.0225544
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adverse childhood family environments and blood pressure differ between men and women

Abstract: BackgroundIt is unclear how adverse childhood family environments differentially impact adult health outcomes among men and women. This brief communication reports on the independent and joint effects of adverse childhood family environments and sex on indicators of health in adulthood.Methods & Results213 18-55-year olds reported on their childhood family environment (Risky Families Questionnaire (RFQ); Family Environment Scale (FEStotal)) and their current perceived stress and depressive and anxious affect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A national cohort study of 12,420 young adults, half of whom were female, found a lower prevalence of hypertension in women who experienced physical abuse (aOR, 0.81; 95% CI, 0.64‐1.01) or had social services involvement (aOR, 0.78; 95% CI, 0.50‐1.22), but again the difference was not statistically significant 36 . In a smaller sample of 213 adults from the greater Pittsburgh area, family conflict and emotional neglect were associated with lower systolic and diastolic blood pressure among women but not among men 34 …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…A national cohort study of 12,420 young adults, half of whom were female, found a lower prevalence of hypertension in women who experienced physical abuse (aOR, 0.81; 95% CI, 0.64‐1.01) or had social services involvement (aOR, 0.78; 95% CI, 0.50‐1.22), but again the difference was not statistically significant 36 . In a smaller sample of 213 adults from the greater Pittsburgh area, family conflict and emotional neglect were associated with lower systolic and diastolic blood pressure among women but not among men 34 …”
Section: Resultsmentioning
confidence: 90%
“…Several studies in this review did not identify a direct relationship between ACEs and a single blood pressure measurement. Moreover, 3 cross‐sectional analyses reported that higher ACE scores were associated with having lower, not higher, blood pressure 27,34,36 . This enigmatic finding should be interrogated further to explore hypotheses such as (1) the differential relationship of the sympathetic nervous system and blood pressure among women versus men 43 and (2) the role of estrogen receptors in the brain on the sympathetic nervous system 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is critical to develop public health and social challenges that improve the lives of children, families, and societies. (Merrick et al, 2019;Schreier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%